2019
DOI: 10.1074/mcp.ra118.001095
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the β4-Integrin Interactome Based on Proximal Biotinylation in the Presence and Absence of Heterodimerization*

Abstract: This study characterized the ␤4integrin interacting proteome using BioID proximity-dependent biotinylation in epithelial MDCK cells. The analysis identified several novel type II hemidesmosome (HD)-associated proteins and revealed potential connecting protein modules that could orchestrate the observed coordinated coassembly of HDs and focal adhesions (FAs). Curiously, unlike the formation of HDs, the assembly of ␤4-interactome did not depend on ␣6␤4heterodimerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…The specificity of these β4 interactors was validated by additional BioID experiments using integrin β4– and IL2R-BirA*–expressing keratinocytes in the absence of biotin to exclude any false-positive interactors. These data are in line with a previous study in which some FA components, such as tensin-3, were identified as interactors of integrin β4 ( Myllymäki et al, 2019 ). Moreover, some of these β4 proximity interactors were validated by Western blotting in the presence or absence of biotin ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…The specificity of these β4 interactors was validated by additional BioID experiments using integrin β4– and IL2R-BirA*–expressing keratinocytes in the absence of biotin to exclude any false-positive interactors. These data are in line with a previous study in which some FA components, such as tensin-3, were identified as interactors of integrin β4 ( Myllymäki et al, 2019 ). Moreover, some of these β4 proximity interactors were validated by Western blotting in the presence or absence of biotin ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…We have identified these bands in a recent study using mass spectroscopy as full-length β4-(β4-FL) and α6-subunits, respectively ( Fig. 1B) [23]. The additional <150 kD fragment, precipitating with an antibody binding to the C-terminus of β4-integrin, was identified as a truncated form of β4-integrin (β4-C) that was lacking most of its extracellular domain.…”
Section: Resultsmentioning
confidence: 90%
“…Scale bars: 10 μm. (D) Venn diagram comparing the α6β4 interactome in keratinocytes with that of β4 in MDCK cells ( Myllymäki et al, 2019 ). Numbers of overlapping and specific proteins are presented.…”
Section: Resultsmentioning
confidence: 99%
“…In simple epithelial tissues and cell lines, such as intestinal and mammary gland cells, integrin α6β4 typically resides in type II HDs ( Uematsu et al, 1994 ; Fontao et al, 1997 ). The group of Aki Manninen used BioID to identify 91 significant cytoplasmic proximity interactors of α6β4 in Madin Darby Canine kidney epithelial cells ( Myllymäki et al, 2019 ) . We compared these interactors with the interactors identified for α6β4 in keratinocytes and found that only 30 proteins were common between the two data sets ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation